Effectiveness of a Brief Psychological Intervention Delivered by Nurse for Depression in Pregnancy: Study Protocol for a Multicentric Randomized Controlled Trial from India. Issue 6 (December 2020) - Raghuveer, Pracheth; Ransing, Ramdas; Kukreti, Prerna; Mahadevaiah, Mahesh; Elbahaey, Wafaa Abdelhakim; Iyengar, Satish; Pemde, Harish; Deshpande, Smita N.
Background: Perinatal depression (PD) has important implications for maternal and infant well-being but largely goes undetected. There is a need to develop low-intensity psychosocial interventions applicable to obstetric health care facilities. Objective: To assess the effectiveness of a brief psychological intervention for mild to moderate PD delivered by a nurse as compared to treatment-as-usual (TAU). Methods: This study is a randomized, open-label, parallel-group, multicentric trial being conducted in four sites of India. A total of 816 pregnant women with mild to moderately severe depression (Patient Health Questionaire-9 score of 5–19) are being assessed for the effectiveness of the intervention. Participants are randomly allocated to two groups of trial intervention (psychological intervention given by nurse) and TAU. The primary outcome is to compare the proportion of women reporting improvement across both groups. Participants are serially followed-up in each trimester and at 6, 10, 14 weeks, and 6 months postpartum. Secondary outcomes include pregnancy outcomes, feeding practices, physical growth, and immunization status of the infants. Conclusion: It is a prospective pregnancy birth cohort with a robust design and long-term follow-up. This is one of the largest studies utilizing non-specialist health workers for the screening and management of PD. This study also holds promise to cast light on the course and outcome of depression during pregnancy in different parts of India. It is envisaged to help in developing a sound screening and referral-based protocol for obstetric settings.